Modified xanthan gum-based gel of curcumin and copper nanoparticles prepared from Tinospora cordifolia for wound therapy - M. V. Patil; N. Singla (Acta Biomedica Scientifica, 2024)
The aim. The synthesis of nanoparticles through green methods is a biologically safe, cost-effective and environmentally friendly approach. This study focuses on the green synthesis of copper nanoparticles using aqueous stem extract of Tinospora cordifolia. Additionally, this research explores the formulation of an acetyl amine-modified xanthan gum-based gel incorporating curcumin and a solution of Cu++ nanoparticles, and investigates its wound healing activity.Materials and methods. The shade-dried stem of Tinospora cordifolia was extracted with distilled water, which serves as a bio-reducing agent for the synthesis of Cu++ nanoparticles. Copper sulphate was added to the extract at room temperature using a magnetic stirrer. The visual color change during the addition indicates the formation of nanoparticles, which was further confirmed by UV spectroscopy and particle size analysis. The  modified xanthan gum-based gel formulation was  prepared using curcumin and a solution of Cu++ nanoparticles, and its wound healing activity was evaluated using the excision method, along with antimicrobial activity assessed by the cup and plate method.Results and discussion. UV absorption was observed at 261 nm, and the particle size was measured at 188 nm, confirming the formation of nanoparticles. The gel containing curcumin and  Cu++ nanoparticles was prepared using modified xanthan gum. The nanocomposite exhibited significant antimicrobial activity against gram-positive bacteria compared to gram-negative bacteria. The group treated with the modified xanthan gum-based curcumin and nano copper composite demonstrated significant wound closure by day 16±2.Conclusion. The  synthesis of  Cu++ nanoparticles using Tinospora cordifolia and the formulation of a gel with modified xanthan gum and curcumin as a drug were successfully achieved. The  gel formulation demonstrated significant antibacterial and wound healing activities, attributed to synergistic effect of Tinospora cordifolia, curcumin, and Cu++ nanoparticles.